CHARACTERISTICS AND LAND QUALITY INDEX IN DRY LAND IN MUARA BATU DISTRICT, NORTH ACEH DISTRICT - JAMIDI; ABDUL RAUF; CHAIRANI HANUM; ERWIN NYAK AKOEB (CV KULTURA DIGITAL MEDIA, 2020)
Soils in dry land generally have low soil quality. This is related with lack of crontrollingfactors of soil fertility such as the low content of organic matter and nutrients. Land on dry landgenerally has low soil quality, this is related to the lack of controlling factors for soil fertilitysuch as low organic matter content and nutrients. Research Objectives To provide a generaldescription of the biophysical conditions of dry land in the West Reuleut Village of North AcehDistrict Muara Batu District and its potential suitability associated with crop development andpatterns. This research was carried out on Dryland West Reuleut Village, Muara Batu District,North Aceh Regency. Flat photography is located at an altitude of + 7 meters above sea level.The study began in August 2017 and ended in April 2018. The study began with pre-researchwith soil sampling. The method used in this study is a semi-detailed survey level free grid surveymethod. Research Results Based on dry land biophysical conditions, especially the conditions ofthe agro-climate zone, then several districts in North Aceh as a limiting factor are nutrientretention of pH and soil organic matter, nutrient availability of N, P, K so that to rehabilitate andoptimize marginal (critical) land in North Aceh district can be done by planting food crops usingintercropping systems